2017
DOI: 10.14423/smj.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Thoracoscopic versus Open Lobectomy: Costs and Outcomes

Abstract: In our study, the VATS group was associated with no reduction in postoperative LOS and a nonsignificant reduction in the amount of time spent in the intensive care unit. Postoperative perception of pain did not vary between either group. Pain perception did, however, correlate strongly with time from operation. Cost did not vary significantly between both groups, with VATS being equivalent to thoracotomy in terms of cost at our institution. In our experience, VATS is an effective, minimally invasive, and safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
5
11
0
Order By: Relevance
“…In the primary and post hoc subanalyses, powered staplers (overall, Ethicon, and Ethicon PVS) were associated with 13.6–17.1% shorter length of stay as compared with manual staplers (overall, Medtronic). Although there are no prior published studies to which we can compare these specific results, the present study’s average hospital LOS (4.7–5.7 days) are in the range of that reported in other US studies [ 6 , 23 , 24 ]. For example, among patients who underwent VATS lobectomy at the University of Kentucky Chandler Medical Center in years 2013–2014, the average hospital LOS was 5.5 days [ 6 ].…”
Section: Discussionsupporting
confidence: 63%
“…In the primary and post hoc subanalyses, powered staplers (overall, Ethicon, and Ethicon PVS) were associated with 13.6–17.1% shorter length of stay as compared with manual staplers (overall, Medtronic). Although there are no prior published studies to which we can compare these specific results, the present study’s average hospital LOS (4.7–5.7 days) are in the range of that reported in other US studies [ 6 , 23 , 24 ]. For example, among patients who underwent VATS lobectomy at the University of Kentucky Chandler Medical Center in years 2013–2014, the average hospital LOS was 5.5 days [ 6 ].…”
Section: Discussionsupporting
confidence: 63%
“…Swanson et al showed similar results and conclusions in their study from 2012, although they disregarded the initial costs of the equipment for VATS [24]. In a retrospective database-review Rodgers-Fischl et al found costs associated with VATS did not vary significantly from thoracotomy, and therefore concluded that in their institution VATS was equivalent to thoracotomy in terms of costs [25].…”
Section: Discussionmentioning
confidence: 68%
“…Our data also show that when cost-conscious intraoperative decisions are made by surgeons, total in-hospital costs of VATSL can be safely reduced to well below the inhospital costs of THORL. Because studies have been inconsistent in demonstrating total in-hospital cost benefits for VATSL over THORL, [11][12][13][14][15] our work provides an explanation for the often higher intraoperative costs associated with VATSL. 14,16,17 Furthermore, given the lower postdischarge costs after VATSL than after THORL, 11,12 our findings suggest that overall costs of the entire episode of care surrounding VATSL will be substantially lower than those of THORL if surgeons make cost-conscious intraoperative decisions.…”
Section: Discussionmentioning
confidence: 81%
“…[1][2][3][6][7][8][9][10] Economic analyses have determined that postdischarge costs are lower after VATSL than after THORL, 11,12 but have been inconsistent in finding an in-hospital cost benefit for VATSL. [11][12][13][14][15] Several studies have suggested that the greater intraoperative costs of VATSL compared with THORL is why overall hospital costs have not been lower for VATSL. 14,16,17 Given the strong shift toward value-based health care, we sought to determine whether the higher intraoperative costs of VATSL compared with THORL 14,16,17 can be favorably impacted by surgeons' intraoperative choices and, if so, whether these more cost-effective choices can be made without adversely affecting outcomes.…”
Section: See Editorial Commentary Page 1278mentioning
confidence: 99%